Imagination in child-development - Turner, Marcia Elizabeth (My University, 1906)
Introduction: To him whose part in life it is, to train the intellect of the child, must come the feeling of vast responsibility at holding in his hand that most delicate of all mechanisms, and knowing that largely on him, depends its destiny. If he takes up his work carelessly, without realizing the importance of his mission, it may result in the downfall of nations; but if he regards it as a sacred charge, to which he must devote his best thought and action, he may succeed in moulding the little mind into the form it was intended to be. Until of late years, child study has been either ignored altogether or at best, studied in an aimless, wholly impracticable way. Some one has said “It is strange that the child should be the last of all God’s creatures, to be studied scientifically”. Now however, parents and teachers are beginning to understand the necessity of a clear conception of the child mind, which knowledge is largely obtained by a thorough acquaintance with him as an individual, during the time when his mind is so rapidly unfolding.
Citation: Turner, Marcia Elizabeth. Imagination in child-development. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Imagination; Intellect; Childhood Development; Education; Theses; Manuscripts (documents)